PKCγ promotes axonal remodeling in the cortico-spinal tract via GSK3β/β-catenin signaling after traumatic brain injury - Zhang, Bo; Li, Zaiwang; Zhang, Rui; Hu, Yaling; Jiang, Yingdi; Cao, Tingting; Wang, Jingjing; Gong, Lingli; Ji, Li; Mu, Huijun; Yang, Xusheng; Dai, Youai; et al. (Scientific reports, 2019)
Traumatic brain injury (TBI) is a common cause of death and disability. Enhancing the midline-crossing of the contralateral corticospinal tract (CST) to the denervated side of spinal cord facilitates functional recovery after TBI. Activation of the gamma isoform of PKC (PKCγ) in contralateral CST implicates its roles in promoting CST remodeling after TBI. In this study, we deployed loss and gain of function strategies in N2a cells and primary cortical neurons in vitro , and demonstrated that PKCγ is not only important but necessary for neuronal differentiation, neurite outgrowth and axonal branching but not for axonal extension. Mechanically, through the phosphorylation of GSK3β, PKCγ stabilizes the expression of cytosolic β-catenin and increase GAP43 expression, thus promoting axonal outgrowth. Further, rAAV2/9-mediated delivery of constitutive PKCγ in the corticospinal tract after unilateral TBI in vivo additionally showed that specifically delivery of active PKCγ mutant to cortical neuron promotes midline crossing of corticospinal fibers from the uninjured side to the denervated cervical spinal cord. This PKCγ-mediated injury response promoted sensorimotor functional recovery. In conclusion, PKCγ mediates stability of β-catenin through the phosphorylation of GSK3β to facilitate neuronal differentiation, neurite outgrowth and axonal branching, and PKCγ maybe a novel therapeutic target for physiological and functional recovery after TBI.